Identification of Plasma Thrombopoietin Level and Its Significance in Patients with Aplastic Anemia and Myelodysplastic Syndrome - Mengying Zhang; Gaochao Zhang; Fangfang Xu; Mengyuan Liu; Xifeng Dong; Weiwei Qi; Huaquan Wang (Global Medical Genetics)
Objective Our objective was to investigate the concentration of plasma thrombopoietin (TPO) in patients with aplastic anemia (AA) and myelodysplastic syndrome (MDS), as well as its relationship with patients' responses to recombined human TPO (rhTPO) therapy.